Scarf Osteotomy with or without Proximal Phalangeal Osteotomy for Severe Hallux Valgus Deformity - Ashok Marudanayagam (Journal of Orthopaedic Surgery, 2014)
Purpose. To report outcome of Scarf osteotomy with or without proximal phalangeal osteotomy for correction of severe hallux valgus deformity. Methods. Records of 48 women and 4 men aged 28 to 68 (mean, 52) years who underwent 57 Scarf osteotomies with or without proximal phalangeal osteotomy for severe hallux valgus by a single surgeon were reviewed. The patients had a hallux valgus angle (HVA) of up to 55°. An additional proximal phalangeal osteotomy was performed in 11 of the patients whose hallux valgus persisted (HVA >10°). The American Orthopaedic Foot and Ankle Society (AOFAS) hallux score, the HVA and intermetatarsal angle (IMA) on radiographs, and the complication rate were assessed. Results. The mean follow-up period was 26 (range, 24–36) months. The mean AOFAS hallux score improved from 57.4 (range, 49–64) to 91.6 (range, 75–100). The mean HVA improved from 38.1° (range, 28°–52°) to 12.8° (range, 5°–20°). The mean IMA improved from 17.0° (range, 13°–24°) to 6.8° (range, 3°–10°). One patient developed chronic regional pain syndrome. There were no instances of non-union, delayed union, or malunion of the osteotomy site. Conclusion. Scarf osteotomy with or without proximal phalangeal osteotomy is an effective treatment for correcting severe hallux valgus deformity.